Determination of In and Sn Mass Fractions in Sixteen Geological Reference Materials by Isotope Dilution MC‐ICP‐MS. Issue 3 (16th April 2018) - Kirchenbaur, Maria; Heuser, Alexander; Bragagni, Alessandro; Wombacher, Frank
Abstract : Mass fractions of Sn and In were determined in sixteen geological reference materials including basaltic/mafic (BCR‐2, BE‐N, BHVO‐1, BHVO‐2, BIR‐1, OKUM, W‐2, WS‐E), ultramafic (DTS‐2b, MUH‐1, PCC‐1, UB‐N) and felsic/sedimentary reference materials (AGV‐2, JA‐1, SdAR‐M2, SdAR‐H1). Extensive digestion and ion exchange separation tests were carried out in order to provide high yields (> 90% for Sn, > 85% for In), low total procedural blanks ( 1 ng for Sn, < 3 pg for In) and low analytical uncertainties for the elements of interest in a variety of silicate sample matrices. Replicate analyses ( n = 2–13) of Sn–In mass fractions gave combined measurement uncertainties (2 u ) that were generally < 3% and in agreement with literature data, where available. We present the first high‐precision In data for reference materials OKUM (32.1 ± 1.5 ng g −1 ), DTS‐2b (2.03 ± 0.25 ng g −1 ), MUH‐1 (6.44 ± 0.30 ng g −1 ) and PCC‐1 (3.55 ± 0.35 ng g −1 ) as well as the first Sn data for MUH‐1 (0.057 ± 0.010 μg g −1 ) and DTS‐2b (0.623 ± 0.018 μg g −1 ). Abstract : Improved chemical digestion and separation of Sn and In from silicate rock matrices Routine isotope dilution MC‐ICP‐MS measurement protocol is presented. Sn and In mass fractions of 16 geological reference materials are presented and discussed.